Conference Presentations and Academic Publishing - Yuriy Gorodnichenko; Tho Pham; Oleksandr Talavera (Institute of Labor Economics (IZA), 2019)
This paper aims to quantify the contribution of conferences to publication success of more than 4,000 papers presented at three leading economics conferences over the 2006- 2012 period. The results show a positive link between conference presentation and the publishing probability in high-quality journals. Participating in major conferences is also associated with improved metrics for other measures of academic success such as the number of citations or abstract views. We document that, while the results are broadly similar across fields, annual meetings of the American Economic Association are particularly valuable in these dimensions.
Keywords: I23; O39; 330; publishing outcomes; research visibility; professional development; conferences